Managing people for productivity : personnel management for profit maximization - Chandra, Durgesh; Karnik, V.G. (New Delhi : South Asian, 1985)
This book deals with human factor in raising productivity. Through various chapters, the book deals the job design, manpower planning, recruitment, selection and induction, transfer, promotion and separation, and people and the performance. The authors have illustrated how a job can be well designed and proper persons fitted to the job. The book also deals with trade unionism, its genesis and growth, and brings about the need for responsible trade unions.
Includes index.
ne 12/07/2018
Loans
Keywords: Personnel management; India